KAJIAN PENAMBAHAN SELULOSA MIKROBIAL NATA DE COCO DAN ZAT ADITIF TERHADAP SIFAT FISIK KERTAS BATANG PISANG ABAKA (Study of The Addition of Microbial Cellulose Nata de Coco and Additives towards Physical Characteristics of Abaca Banana Stem Based Paper) - Fitriani, Fitriani; Mahidin, Mahidin; Said, Syahiddin Dahlan; Busthan, Meuthia (Baristand Industri Banda Aceh, 2016)
Utilization of cellulose derived from wood as a raw material for pulp and paper inIndonesia increases gradually. This condition leads to deforestation in Indonesia and causes various sideeffects on the environment. The objective of this research is to study the effect of the addition of microbialcellulose nata de coco and additives towards physical characteristics of abaca banana stem paper byusing Peroxide Alkaline Pulping (APP) method. The combination of microbial cellulose pulp nata de cocoand banana stem pulp ratio of 0:100 ; 25:75 ; 50:50 ; 75:25 ; 100:0 and the addition of additives to themix the pulp with variations (b/b): without additives, tapioca (1%, 3% and 5%) and kaolin (5%, 10%, and15% used in the process of forming a sheet of paper. The results showed the addition of a bit of microbialpulp cellulose and pulp stems of the banana abaca could improve the physical strength of paper withgrammage 157.13 gr/mÂ², a thickness of 0.0058 mm, water content of 4.48%, water absorption of 22.21%,tensile resistance 5 kN/m and elongation of 38.59%.